Whom do you know? Recruiters' motives for assessing jobseekers' online networks. Issue 8 (28th April 2021) - Hedenus, Anna; Backman, Christel; Håkansson, Peter
Abstract: Network recruitment has become an essential part of the modern labour market. However, there are significant research gaps: 1) the development of social media has been crucial to the growth of social networks, yet we know little about its influence on network recruitment; 2) studies on network recruitment generally focus on employees' rather than employers' perspectives; 3) the context of most research is the US labour market, which then identifies a need for contributions relating to other countries. The aim of this study is to analyse and discuss recruiters' use of SNS to evaluate the networks of potential candidates. To understand how and why recruiters assess online networks, we used qualitative data from a Swedish study. Our analysis showed that recruiters search the internet either to find information that helps them ascertain the candidate as trustworthy, or to evaluate the candidate's social capital through the size and composition of their networks. For certain job positions especially, active management of one's online networks thus becomes crucial. Finally, this study illustrates how network connections may undermine rather than build trust, and thereby challenges a belief in the positive impact of networks.